Prof. Salazar's empire and the ministerial elite of the New State (1933-1945) - Costa Pinto, António (2001)
This article analyses the problem of political decision, of the composition and the means of recruitment of the ministerial elite of salazarism. After systematisation of some elements of comparison with Franco-ism, Italian fascism, and national-socialism, this work contributes with the theory that the greater or lesser role of the sole party in these political systems is the most important explanatory factor for diversity whether of political decision or of the composition of the ministerial elite of these dictatorships of the «fascist era».